Study of a deep draft vessel to enhance onsite installation capability of a jack up type unit operating in the wind farm zone offshore of the Taichung Harbor Taiwan. (1st December 2020) - Kehr, Y.Z.; Chang, G.A.; Huang, G.J.; Weng, W.K.
Abstract: In the paper, a concept of placing a deep draft vessel upstream a jack up type unit is proposed to enhance onsite installation capability of the jack up type unit operating in the wind farm zone offshore of the Taichung Harbor Taiwan, where water depth is less 50m and bottom fixed structures are used. The deep draft vessel intends to induce wave shielding effect to reduce the motions of the downstream jack up type unit during the initial phase of its onsite installation, while its legs/spudcans are not yet touching the seabed and it is still in free floating condition. In general, the more the motion of the jack up type unit is reduced during the initial phase of its onsite installation, the more its onsite installation capability is enhanced. ANSYS AQWA is utilized to analyze the motions of the two floating bodies, the deep draft vessel and the jack up type unit, as well as the wave shielding effect for various wave periods and incident angles. In the analysis, fluid is assumed ideal, and no viscous effect is considered in the calculation of all the motions of the two floating bodies. Pitch and heave motion RAOs (Response Amplitude Operator) of the jack up unit with or without the deep draft vessel placing upstream are compared to examine the wave shielding effect. In the study, a parametric study for a range variation of the principal dimensions of the two floating bodies is performed to determine suitable principal dimensions for the deep draft vessel and the feasibility of the proposed concept. In addition, pitch and heave motion RAOs of the deep draft vessel at wave incident angles of 0°~30° are also analyzed to evaluate its seakeeping performance. From the results of the study, it is found that the vessel with deeper draft (≥12.5 m) is more effective to induce wave shielding effect in waves with period of 5–7 s. The deeper the draft of the vessel, the greater the wave shielding effect, and the more motion reduction to the downstream jack up type unit in waves with period of 5–7 s. It is also found that, in waves with period of 5–7 s and at incident angles of 0°~30°, the vessel with deeper draft has better seakeeping performance. Since the most common waves in the wind farm zone offshore of the Taichung Harbor Taiwan are of 6–7 s in period, the feasibility of the concept of placing a deep draft vessel upstream a jack up type unit to reduce the motion and enhance the onsite installation capability of the jack up type unit operating in that area is demonstrated. Highlights: Motions of a free-floating jack up in waves is selected to examine its onsite installation capability. Onsite installation capability of a jack up can be enhanced by placing a deep draft vessel upstream. The deeper the draft of a deep draft vessel, the more motion reduction of a jack up downstream the vessel. A smaller size jack up with a deep draft vessel upstream has less motions than that of a larger size jack up alone. A deep draft vessel with deeper draft can have better seakeeping performance in head sea.